Development of a Financial Information System Website at Gkii Muara Asa Church - Setiawan, Hendri; Ekawati, Hanifah; Harianto, Kusno (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2025)
Financial management in GKII Muara Asa Church has traditionally been conducted manually using physical books and spreadsheets, making it prone to recording errors, reporting delays, and lack of transparency for church members. To address these issues, a web-based Financial Information System (FIS) website was developed to facilitate transaction input, digital data storage, real-time financial reporting, and information access for members. The system was built using the Waterfall model of the System Development Life Cycle (SDLC), including planning, analysis, design, implementation, testing, and maintenance phases. Technologies used include Laravel as the backend, MySQL for database management, and Bootstrap for frontend development. Functional testing showed that all core features such as login, transaction input, data search, and backup operate as expected with an average response time under 2 seconds. The implementation proves that the system successfully improves efficiency, accuracy, and transparency in church financial management.